A Cross Sectional Study on Various Menstrual Hygiene Products Used Among College Going Students of Central Gujarat, India - Bavadiya, Bhoomi; Thakur, Dhruvi (International Journal of Medical Students, 2023)
BACKGROUND: In recent years, there has been significant progress in raising awareness about menstruation in Indian society, primarily through educational initiatives and various communication channels. However, one critical aspect that often remains overlooked is menstrual hygiene products. This study aims to bridge this knowledge gap by conducting a quantitative assessment of students' preferences, their level of knowledge, reliability ratings, and acceptability of various menstrual hygiene products. Additionally, the secondary objective is to identify the common challenges and discomforts frequently experienced by women when using these hygiene products. METHODS: This study takes on a descriptive approach, primarily focusing on assessing the knowledge, attitudes, and practices related to menstrual hygiene products among young females. Data for this study was collected through online questionnaires and meticulously organized in Excel sheets for comprehensive analysis. RESULTS: Our research involved 186 medical students, the majority of whom displayed a good understanding of menstrual hygiene products and their usage. It is noteworthy that 75% of the students reported facing issues while using these products. However, these challenges did not significantly disrupt their daily activities, indicating their resilience and adaptability in managing these difficulties. CONCLUSION: Disposable pads emerged as the favored menstrual hygiene product among the participants due to their convenience, hygiene, comfort, and high absorption capacity. Nevertheless, it is crucial to acknowledge that users of disposable pads often encounter issues such as skin irritation, leakage, unpleasant odors, and a potential risk of infection. This underscores the need for continuous efforts to improve product design and education surrounding menstrual hygiene to ensure the well-being and comfort of women.